Legal Policy for Drug Users in Indonesia and the Netherlands (Universitas Negeri Semarang, 2022)
Indonesia does not allow the use of narcotics except for medical purposes. Drug use for medical purposes must be under supervision of doctor, regardless of the level of content in it. In contrast to Netherlands, which allows the use of Soft Drugs as regulated in Dutch Opium Act. In Netherlands itself, the use of marijuana and the purchase of marijuana can be done at a coffee shop that already has a permit. The legalization of certain types of drugs and for certain purposes exists because Netherlands wants to provide legal certainty for their people. Netherlands want drug trafficking not to be carried out by crime syndicates that will harm their people. In addition, Netherlands also provides adequate health facilities for drug addicts. Evidently, number of addicts, number of HIV infections due to injection needles, and deaths from drugs has decreased. This is what distinguishes drug policy in Indonesia and Netherlands. Indonesia prioritizes the Penal Policy, it can be seen from the punishment of drug users. While Netherlands prioritizes Non-penal Policy, it can be seen from the incessant drug control. What can Indonesia follow from the drug policy in Netherlands is the prevention of drugs with state control over drug trafficking accompanied by adequate health facilities. Indonesia should reduce the punishment of drug addicts. Criminalizing drug addicts will not solve the problems. In the case of drug abuse, addicts are also victims.